Fatigue strength of a tensile-shear loaded clinched joint made from an al-5052 alloy sheet - Han, J.; T. Hwang, W.; E. Lee, C.; K Kim, H. (International Journal of Engineering and Technology, 2020)
The clinching process has been shown to be able to join dissimilar material sheets as an alternative to spot welding. In this study, monotonic and fatigue tests were conducted using tensile-shear specimens for an evaluation of the strengths of a joint. In the fatigue tests, an interface failure occurred. The fatigue ratio of the joint is 0.29, assuming a fatigue endurance limit at 2 x106 cycles. The maximum von-Mises stress of the joint at the load amplitude corresponding to the fatigue endurance limit is slightly higher than the yield strength of Al-5052 alloy. This indicates that the strength of the neck region is increased partially due to work hardening.Â Â Â